-5(5x-5)+3=-25x+28

Simple and best practice solution for -5(5x-5)+3=-25x+28 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(5x-5)+3=-25x+28 equation:



-5(5x-5)+3=-25x+28
We move all terms to the left:
-5(5x-5)+3-(-25x+28)=0
We multiply parentheses
-25x-(-25x+28)+25+3=0
We get rid of parentheses
-25x+25x-28+25+3=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0

You can always share this solution

See similar equations:

| 7c+12=-4c(78+12) | | 16x^2-56x+37=0 | | 1/4+x-1/3=2/3+3+1/4 | | -1/4w=7 | | 33=4x-7x+6 | | 4=4(x+3) | | 25=-2(5h+3) | | (6^x)=(1/216) | | x^2+22x=8 | | 2+2(3x-4)=8x | | |-3r|=9 | | 69=1+2(4-5x) | | F(x)=-3+4 | | |3x|=9 | | 1.5(x+4)–3=4.5(x–2) | | 2x?2???28x+98=0 | | ?4=x/20?5 | | 9.34=x-2.7 | | 3(5b+5)+6=81 | | 6x-14=-2x+10 | | 8-8(7n-7)=176 | | 12x+1=3(4x+1)–2 | | 3(h+4)=18 | | 2(x-5)^2=-32 | | 124=4(1+5a) | | Y=-3/2x+8 | | 16-10=4q | | 2x+3-4x+7=5 | | 6w-8=4w+2 | | 1/4x+1/2=13 | | 7/12=3/x | | 2s+s=10 | | 9/8=g+(1/2) | | 13x=63 | | (2x-3)^2=0 | | X^2-0.6x+0.09=29.16 | | 7/6=x/8+5/8 | | -3x+12=-21+8x | | -2=-2x^2-3x | | 40+22j=26 | | 5x-15/2-1=14 | | 5.3=z=2.7 | | 1/4(4x+40)=2x+10-x | | -3/4(24x-4)+2(x-3)=3x-48 | | 3x+1=253 | | (4^x)=(1/16) | | 9f-8=20 | | 159.01=6x+20.05 | | 3y?1=14 | | 16/3*n=1 | | 19+4=-8(9r-7) | | -3r=15r+2 | | 8x+9x-6x=38+6 | | 2r+49=59 | | (300-w)w=21600 | | 4(-6m-10)=-16 | | x^2+7 | | 10(y+3)-6(y+1)=2y | | 3(q+1)-q=23 | | -12=4/5x | | r=-5r+2 | | 7x4?17=1?27x?114 | | -3(6p+4)-2(1-14p)=3(4+3p) | | 7w=81 | | x+4/6=5/6-x-1/3 |